PROSPECTS FOR THE APPLICATION OF DISTRIBUTED LEDGER TECHNOLOGY TO IMPROVE FINANCING OF START-UP (JAPAN EXPERIENCE) - S. S. Matveevskii (Вестник университета)
A project on the use of distributed registry technology to improve funding for start-ups in Japan has been considered. The project is based on the application of distributed registry technology, smart contracts, a big database of start-ups credit risk (in Japan CRDS), a local investment fund, a unified marketing and trading platform. The model of investor behavior (taking into account risk and profitability) has made it possible to show, that with growing investor confidence (individuals and households) and a certain level of profitability of startups, investing in startups will be more preferable, than a bank deposit. The features of the project have been highlighted and a conclusion has been made, that under certain conditions, the adduced scheme for financing start-ups can be used in Russia, for example, by the Industry Development Fund.